Implementasi Undang-Undang Nomor 19 Tahun 2016 Tentang Informasi dan Transaksi Elektronik (Uu Ite) terhadap Pelaku Judi Online dan Penegakkan Perjudian Online di Kabupaten Garut - Ahya Amalia Deyanti; Neni Ruhaeni (UNISBA Press, 2024)
Abstract. This study aims to analyze the implementation and enforcement of criminal law against online gambling perpetrators in Indonesia based on Law Number 19 of 2016 concerning Electronic Information and Transactions. The research method used is normative legal research. Data collected includes regulations related to online gambling, court decisions, and relevant literature. The analysis is conducted by identifying legal provisions governing online gambling, examining the implementation of criminal law enforcement, and evaluating its effectiveness. The research results show that Law Number 19 of 2016 concerning Electronic Information and Transactions has strengthened the legal basis for taking action against online gambling perpetrators, as stipulated in Article 27 Paragraph (2) of the law, which prohibits